The commercial NLP landscape in 2017. (5th June 2017) - DALE, ROBERT
Abstract: The commercialisation of natural language processing began over 35 years ago, but it's only in the last year or two that it's become substantially more visible, largely because of the intense popular interest in artificial intelligence. So what's the state of commercial NLP today? We survey the main industry categories of relevance, and offer comment on where the action is today.